BASQARIW FUNKCIYALARI HAQQINDA ALIM A.T.TUXTABAEVTIŃ KÓZQARASLARI - Erejepov, M. (ILIM hám JÁMIYET, 2022)
This article presents the valuable views of the scientist A.T.Tukhtabaev on the functions of management, management theory, administrative management. It highlights recommendations on the management functions that are most necessary for the manager and are important for the correct implementation of management activities.